EDTA stabilizes the concentration of platelet-derived extracellular vesicles during blood collection and handling. (4th July 2022) - Buntsma, Naomi C.; Gąsecka, Aleksandra; Roos, Yvo B.W.E.M.; van Leeuwen, Ton G.; van der Pol, Edwin; Nieuwland, Rienk
Abstract: Citrate is the recommended anticoagulant for studies on plasma extracellular vesicles (EVs). Because citrate incompletely blocks platelet activation and the release of platelet-derived EVs, we compared EDTA and citrate in that regard. Blood from healthy individuals (n = 7) was collected and incubated with thrombin receptor-activating peptide-6 (TRAP-6) to activate platelets, subjected to pneumatic tube transportation (n = 6), a freeze-thaw cycle (n = 10), and stored before plasma preparation (n = 6). Concentrations of EVs from platelets (CD61 + ), activated platelets ( P -selectin + ), erythrocytes (CD235a + ), and leukocytes (CD45 + ) were measured by flow cytometry. Concentrations of EVs from platelets and activated platelets increased 1.4-fold and 1.9-fold in EDTA blood upon platelet activation, and 4.2-fold and 9.6-fold in citrate blood. Platelet EV concentrations were unaffected by pneumatic tube transport in EDTA blood but increased in citrate blood, and EV concentrations of erythrocytes and leukocytes were comparable. The stability of EVs during a freeze-thaw cycle was comparable for both anticoagulants. Finally, the concentration of platelet EVs was stable during storage of EDTA blood for six hours, whereas this concentration increased 1.5-fold for citrate blood. Thus, EDTA improves the robustness of studies on plasma EVs.